Empirical Study of Convergent-Divergent Trends in Innovation EU Countries Development - Liudmyla Smoliy; Alina Burliai; Inna Novak; Alla Revutska; Nina Pitel (Наукові горизонти, 2022)
The article is devoted to the problem of disproportionate innovation development in the European Union and the impact of these processes on economic growth. The aim of the work is an empirical study of the unevenness and asymmetry of innovation spending in the EU and analysis of convergent-divergent trends in this area. The results of recent research show a desire to strengthen cooperation in the field of innovation, which changes the situation in a positive direction and proves the signs of convergence of innovation, and they are most pronounced in the least developed regions of Europe. The urgency of solving this scientific problem is that the internal convergence of the European Union in the field of policy to support research, development and innovation is one of the strategic goals of the association. Models based on the concept of convergence have become a methodological tool for determining the asymmetry of development. The study was conducted on the basis of analysis of statistical data of 28 European Union countries for the period 2008-2019. The article presents the results of an empirical analysis of the asymmetry of innovative development of EU countries in terms of research and development. It is established that there is a shift towards increasing the share of R&D expenditures in GDP. Convergent tendencies in terms of development asymmetry, σ-convergence and β-convergence are revealed. The study empirically confirms and theoretically proves that the reduction of differentiation and convergence of countries is manifested in increased funding for innovation in countries lagging behind in these parameters. The practical significance of the results of the study lies in the possibility of their use to assess the effectiveness of innovation policy in the European Union